Genetic diversity of Lecanicillium lecanii and its pathogenicity against Diaphorina citri - Lu Lianming; Cheng Baoping; Du Danchao; Hu Xiurong; Pu Zhanxu; Chen Guoqing (浙江大学学报. 农业与生命科学版)
Diaphorina citri may be the most serious pest of citrus worldwide, primarily because it is the vector of huanglongbing (HLB), one of the most destructive citrus diseases, and can damage citrus directly by feeding fresh shoots and cause citrus sooty mold disease. Currently, control of D. citri mainly depends on the chemical pesticides. However, pesticides abuse affects workers and food safety, causes the development of insecticide-resistant D. citri populations, and reduces populations of natural enemies in citrus orchards. Therefore, new approaches are needed to complement the existing management strategies against D. citri.Lecanicillium lecanii, formerly named Verticillium lecanii, is an entomopathogenic fungus with a remarkably wide host range, which can infect aphids, whiteflies, trips, plant hoppers and so on. Infection of L. lecanii against D. citri was firstly reported in 1980s. However, from then on, there is no further research such as biological characteristic and pathogenicity difference about this fungus. Therefore, in this study, genetic diversities of 19 L. lecanii strains from different hosts and geographical origins as well as their biological characteristics and pathogenicities against D. citri were determined and analyzed. This research aimed to understand the genetic diversity, pathogenicity difference and their relationships with geographical origins, host varieties and biological characteristics.Firstly, 19 L. lecanii strains from different hosts and geographical origins were characterized using randomly amplified polymorphic DNA (RAPD) analysis. Based on the RAPD results, a dendrogram was constructed using unweighted pair group method with arithmetic mean (UPGMA) by software NTSYS-pc version 2.1. Then, the ITS1-5.8S rDNA-ITS2 andβ-tubulin genes of these L. lecanii strains were amplified and sequenced using primer sets ITS5/ITS4 and Bt2a/Bt2b, respectively. These sequences were aligned with software ClustalX 2.0, edited with software BioEdit 7.2.5, and finally a phylogenic tree was constructed using the neighbor-joining method by software MEGA 5.05. Besides, the biological characteristics of these strains such as mycelial growth rates, sporulation quantities, conidial germination rates and conidial sizes were also determined. Furthermore, the pathogenicities of these strains against D. citri were assayed, and the invasion process of strain ZJVL-A was observed under a dissecting microscope, a scanning electron microscope and a light microscope.The results showed that a total of 96 polymorphic bands were amplified using 7 random primers, and the size of the bands ranged from 0.2 3 kb. All the 19 L. lecanii strains were divided into 2 groups in the UPGMA dendrogram. Strain CGVL-11 was located alone in one group, while the other strains were clustered into another group. In the latter group, 18 strains were then divided into 2 subgroups. The ITS1-5.8S rDNA-ITS2 and β-tubulin gene sequences had been deposited in GenBank and their accession numbers were KJ598810 KJ598828 and KJ598829-KJ598847, respectively. The similarities of ITS1-5.8S rDNA-ITS2 and β-tubulin gene sequences were 98%-100% and 96%-100% with each other, and molecular variations existed within these nucleotide sequences. The phylogenetic tree based on ITS1-5.8S rDNA-ITS2 and β-tubulin sequences was consistent with the dendrogram generated through RAPD analysis. The mycelial growth rates, sporulation quantities, conidial germination rates and conidial sizes of these strains were remarkably different. The colony diameter was 4.25-2.85 cm after 10 d incubation, and the sporulation quantity was 0.10×108-9.75×108 conidia/mL after 3 d incubation in PDB medium, and the conidial germination rate was 3.55%-68.38% after 8 h incubation at 25 ℃, and the size of conidia was 4.0-5.0 μm in length and 1.4-1.7 μm in width. Conidia of L. lecanii strain ZJVL-A mainly distributed in the intersegmental fold, setal alveolus, anus, genital, and other fold or sunken regions on every tagmata. At 16 h post-inoculation, the conidia began to germinate and penetrated the cuticle of host. At 42 h post-inoculation, the hyphae invaded into haemocoel, proliferated abundantly and filled the entire haemocoel. Diaphorina citri was killed by the fungus after 54 h post-inoculation. After 60 h post-inoculation, the internal organs of host such as fat body, muscle tissue, digestive tract and ovary were invaded and progressively degraded. Finally, a large number of newly-developed conidia could be observed on the hyphae which covered the body surface of host.In conclusion, genetic diversities and pathogenicity differences exist in populations of L. lecanii. Moreover, their biological characteristics also show significant differences. However, they have no relationship with each other and with host varieties or geographical origins. The strain ZJVL-A maybe kill D. citri through secreting some toxins before the hyphae degrade the internal organs of host. This research lays a good foundation for further study on the pathogenic mechanism of L. lecanii against D. citri, and takes an important step towards developing and utilizing these entomopathogenic fungi for their potential to suppress D. citri populations.